2012
DOI: 10.1126/scitranslmed.3004108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correction of Human Induced Pluripotent Stem Cells from Patients with Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA) is among the most common genetic neurological diseases that cause infant mortality. Induced pluripotent stem cells (iPSCs) generated from skin fibroblasts from SMA patients and genetically corrected have been proposed to be useful for autologous cell therapy. We generated iPSCs from SMA patients (SMA-iPSCs) using nonviral, nonintegrating episomal vectors and used a targeted gene correction approach based on single-stranded oligonucleotides to convert the survival motor neuron 2 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
3
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(219 citation statements)
references
References 45 publications
10
200
3
6
Order By: Relevance
“…Our data in iPSC-derived SMA I MN models confirmed previously published data showing marked reduction of SMN expression and gem counts [23,47]. SMN expression level in SMA III and asymptomatic showed mildly reduced levels in iPSC and smNPCs and no difference in MNs as compared to controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data in iPSC-derived SMA I MN models confirmed previously published data showing marked reduction of SMN expression and gem counts [23,47]. SMN expression level in SMA III and asymptomatic showed mildly reduced levels in iPSC and smNPCs and no difference in MNs as compared to controls.…”
Section: Discussionsupporting
confidence: 91%
“…A cornerstone of SMA pathology in SMN1-deleted individuals is low SMN expression which was already demonstrated in iPSC-derived SMA I models [23,47].…”
Section: Pls3 Was Highly Upregulated In Mixed Mn Cultures Of Asymptommentioning
confidence: 79%
“…More recently, work by Corti and colleagues demonstrated that MNs differentiated from genetically corrected SMA iPSCs could survive transplantation and correctly engraft in the spinal cord of a one-day-old mouse model of SMA (Corti et al, 2012). Furthermore, these cells could ameliorate disease phenotypes and extend the life span of SMN mutant mice, at least in part by providing neurotrophic support (Corti et al, 2012). It has also been shown that ESC-derived MNs, when transplanted into the tibial nerve of adult animals can form functional NMJs and ameliorate muscle atrophy caused by nerve transection (Yohn, et.…”
Section: Formation Of Nmjs and In Vivo Engraftmentmentioning
confidence: 99%
“…37 The correction of SMN gene, using singlestranded oligonucleotide, was shown to restore the SMN gene profile in neurons derived from SMA-iPSC, converting SMN2 in SMN1. 38 It is possible that for SMA, transient rescue of the developmental loss of SMN may be sufficient to confer efficacy, which may not be the case for other neurodegenerative diseases where long-term degeneration of the transplanted cells is a valid concern.…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%